2016
DOI: 10.1099/mgen.0.000071
|View full text |Cite
|
Sign up to set email alerts
|

Integrated computational prediction and experimental validation identifies promiscuous T cell epitopes in the proteome of Mycobacterium bovis

Abstract: The discovery of novel antigens is an essential requirement in devising new diagnostics or vaccines for use in control programmes against human tuberculosis (TB) and bovine tuberculosis (bTB). Identification of potential epitopes recognised by CD4+ T cells requires prediction of peptide binding to MHC class-II, an obligatory prerequisite for T cell recognition. To comprehensively prioritise potential MHC-II-binding epitopes from Mycobacterium bovis, the agent of bTB and zoonotic TB in humans, we integrated thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 63 publications
0
18
0
Order By: Relevance
“…Therefore, the next step to take will be to experimentally validate that the predicted epitopes are presented and recognized in the cow immunological context, and that they are capable of eliciting immunogenic responses. Despite being based on predictions, the goodness of currently available tools for this purpose has been acknowledged by several authors and the use of prediction tools is seen as a great aid for the identification of new epitopes [19,[36][37][38]. Since the protein space of trypanosomes, particularly T. congolense, T. evansi, and T. vivax remains largely unexplored, the majority of the antigens of origin of the predicted epitopes were either uncharacterized proteins or had low annotation scores inferred by homology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the next step to take will be to experimentally validate that the predicted epitopes are presented and recognized in the cow immunological context, and that they are capable of eliciting immunogenic responses. Despite being based on predictions, the goodness of currently available tools for this purpose has been acknowledged by several authors and the use of prediction tools is seen as a great aid for the identification of new epitopes [19,[36][37][38]. Since the protein space of trypanosomes, particularly T. congolense, T. evansi, and T. vivax remains largely unexplored, the majority of the antigens of origin of the predicted epitopes were either uncharacterized proteins or had low annotation scores inferred by homology.…”
Section: Discussionmentioning
confidence: 99%
“…For the prediction of CD4 T-cell epitopes we used the IEDB recommended method, the MHC II binding predictions tool (http://tools.iedb.org/mhcii/) [18], over the invariant proteome file. Given that no bovine lymphocyte antigen (BoLA) alleles are available for this tool we ran the program against the set of human leukocyte antigens (HLAs), as described elsewhere [19]. We considered for further analysis only the 0.01% top scoring CD4 T-cell epitopes that were predicted on the T. cruzi-masked proteome file.…”
Section: Prediction Of T-cell Epitopesmentioning
confidence: 99%
See 1 more Smart Citation
“…Since there are no available SLA class II alleles for this tool, we used the HLA class II reference set consisting of 27 alleles available at IEDB [ 81 ]. It has been described that HLA-II can be used to approximate predictions for other mammals [ 82 ].…”
Section: Methodsmentioning
confidence: 99%
“…Majority of MHC class II epitope binding algorithm used prediction towards human leukocyte antigens (HLA) as compared to other leukocyte antigens particularly bovine leukocyte antigens (BoLA). However, it was found that there was a certain pseudo-sequence (representation of the MHC-II complex polymorphic binding pockets) similarity between both species' alleles to approximate the protein binding in bovine (Farrell et al, 2016). Hence, the application of the selected HLA alleles that were found shown to be similar to BoLA by Farrel et al (2016).…”
Section: Prediction Of Outer Membrane Proteins' Antigenicitymentioning
confidence: 99%